ORGANIZATIONAL AND LEGAL MEANS OF REGULATING CONFLICT OF INTEREST IN STATE AUTHORITY BODIES - Panova, Oksana; Avdyushkina, Karyna (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2025)
The purpose of the article is to analyze the organizational and legal means of resolving conflicts of interest in state authorities, through the use of legislative instruments, institutional mechanisms, preventive measures, declaration and verification mechanisms, sanctions and liability. Research methods: a comprehensive analysis of regulatory legal acts, scientific literature and the practice of applying domestic legislation, including measures of both administrative and criminal legislation, was used. Results: it is substantiated that organizational and legal means are an important component of the system for resolving conflicts of interest. They provide a legal basis for preventing conflicts of interest, establish ethical standards of behavior and contribute to increasing the transparency of public administration. It is noted that an effective system for resolving conflicts of interest helps to strengthen public trust in state authorities and improves the quality of administrative decision-making. It is determined that the legislative support of anti-corruption policy, the work of specialized bodies, such as the National Anti-Corruption Commission, the National Anti-Corruption Bureau and the Administrative Prosecutor’s Office - these institutions perform the functions of investigation, prevention and control over compliance with anti-corruption requirements, which contributes to the identification and punishment of corrupt officials in Ukraine. However, effective combating of corruption requires a comprehensive approach. Discussion: organizational and legal means of resolving conflicts of interest involve the establishment of legislative, normative and regulatory instruments that determine the processes and mechanisms for preventing, identifying, investigating and eliminating conflicts of interest.